Structural modelling of substrate binding and inhibition in penicillin V acylase from pectobacterium atrosepticum - Avinash, Vellore Sunder; Panigrahi, Priyabrata; Suresh, C. G.; Pundle, Archana V.; Ramasamy, Sureshkumar (Biochemical and Biophysical Research Communications, 2013)
Penicillin V acylases (PVAs) and bile salt hydrolases (BSHs) have considerable sequence and structural similarity; however, they vary significantly in their substrate specificity. We have identified a PVA from a Gram-negative organism, Pectobacterium atrosepticum (PaPVA) that turned out to be a remote homolog of the PVAs and BSHs reported earlier. Even though the active site residues were conserved in PaPVA it showed high specificity towards penV and interestingly the penV acylase activity was inhibited by bile salts. Comparative modelling and docking studies were carried out to understand the structural differences of the binding site that confer this characteristic property. We show that PaPVA exhibits significant differences in structure, which are in contrast to those of known PVAs and such enzymes from Gram-negative bacteria require further investigation. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bile salt hydrolase; docking; Homology modelling; Inhibition; Pectobacterium; Penicillin acylase

Structure of highly active BSH enzyme with subordinated post-translational excision - Chand, Deepak; Panigrahi, Priyabrata; Ramasamy, Sureshkumar; Suresh, C. G. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Bile salt hydrolase; Mutagenesis; X-ray crystallography

Sequence and structure-based comparative analysis to assess, identify and improve the thermostability of penicillin G acylases - Panigrahi, Priyabrata; Chand, Deepak; Mukherji, Ruchira; Ramasamy, Sureshkumar; Suresh, C. G. (Journal of Industrial Microbiology & Biotechnology, 2015)
Penicillin acylases are enzymes employed by the pharmaceutical industry for the manufacture of semi-synthetic penicillins. There is a continuous demand for thermostable and alkalophilic enzymes in such applications. We have carried out a computational analysis of known penicillin G acylases (PGAs) in terms of their thermostable nature using various protein-stabilizing factors. While the presence of disulfide bridges was considered initially to screen putative thermostable PGAs from the database, various other factors such as high arginine to lysine ratio, less content of thermolabile amino acids, presence of proline in beta-turns, more number of ion-pair and other non-bonded interactions were also considered for comparison. A modified consensus approach designed could further identify stabilizing residue positions by site-specific comparison between mesostable and thermostable PGAs. A most likely thermostable enzyme identified from the analysis was PGA from Paracoccus denitrificans (PdPGA). This was cloned, expressed and tested for its thermostable nature using biochemical and biophysical experiments. The consensus site-specific sequence-based approach predicted PdPGA to be more thermostable than Escherichia coli PGA, but not as thermostable as the PGA from Achromobacter xylosoxidans. Experimental data showed that PdPGA was comparatively less thermostable than Achromobacter xylosoxidans PGA, although thermostability factors favored a much higher stability. Despite being mesostable, PdPGA being active and stable at alkaline pH is an advantage. Finally, several residue positions could be identified in PdPGA, which upon mutation selectively could improve the thermostability of the enzyme.
Keywords: Alkalistable; beta-lactam antibiotics; Consensus approach; Disulfide bridge; Ion pairs; Penicillin acylase; Thermostability

Structure mediation in substrate binding and post-translational processing of penicillin acylases: Information from mutant structures of Kluyvera citrophila penicillin G acylase - Chand, Deepak; Varshney, NishantKumar; Ramasamy, Sureshkumar; Panigrahi, Priyabrata; Brannigan, James A.; Wilkinson, Anthony J.; Suresh, C. G. (Protein Science, 2015)
Penicillin acylases are industrially important enzymes for the production of 6-APA, which is used extensively in the synthesis of secondary antibiotics. The enzyme translates into an inactive single chain precursor that subsequently gets processed by the removal of a spacer peptide connecting the chains of the mature active heterodimer. We have cloned the penicillin G acylase from Kluyvera citrophila (KcPGA) and prepared two mutants by site-directed mutagenesis. Replacement of N-terminal serine of the beta-subunit with cysteine (Ser beta 1Cys) resulted in a fully processed but inactive enzyme. The second mutant in which this serine is replaced by glycine (Ser beta 1Gly) remained in the unprocessed and inactive form. The crystals of both mutants belonged to space group P1 with four molecules in the asymmetric unit. The three-dimensional structures of these mutants were refined at resolutions 2.8 and 2.5 angstrom, respectively. Comparison of these structures with similar structures of Escherichia coli PGA (EcPGA) revealed various conformational changes that lead to autocatalytic processing and consequent removal of the spacer peptide. The large displacements of residues such as Arg168 and Arg477 toward the N-terminal cleavage site of the spacer peptide or the conformational changes of Arg145 and Phe146 near the active site in these structures suggested probable steps in the processing dynamics. A comparison between the structures of the processed Serb1Cys mutant and that of the processed form of EcPGA showed conformational differences in residues Arg alpha 145, Phe alpha 146, and Phe beta 24 at the substrate binding pocket. Three conformational transitions of Arg alpha 145 and Phe alpha 146 residues were seen when processed and unprocessed forms of KcPGA were compared with the substrate bound structure of EcPGA. Structure mediation in activity difference between KcPGA and EcPGA toward acyl homoserine lactone (AHL) is elucidated.
Keywords: acyl homoserine lactone; autocatalytic processing; conformational changes; KcPGA_Ser beta 1Cys; KcPGA_Ser beta 1Gly; Ntn hydrolase

Structural analysis of a penicillin V acylase from pectobacterium atrosepticum confirms the importance of two Trp residues for activity and specificity - Avinash, Vellore Sunder; Panigrahi, Priyabrata; Chand, Deepak; Pundle, Archana; Suresh, Cheravakattu Gopalan; Ramasamy, Sureshkumar (Journal of Structural Biology, 2016)
Penicillin V acylases (PVA) catalyze the deacylation of the beta-lactam antibiotic phenoxymethylpenicillin (Pen V). They are members of the Ntn hydrolase family and possess an N-terminal cysteine as the main catalytic nucleophile residue. They form the evolutionarily related cholylglycine hydrolase (CGH) group which includes bile salt hydrolases (BSH) responsible for bile deconjugation. Even though a few PVA and BSH structures have been reported, no structure of a functional PVA from Gram-negative bacteria is available. Here, we report the crystal structure of a highly active PVA from Gram-negative Pectobacterium atrosepticum (PaPVA) at 2.5 angstrom resolution. Structural comparison with PVAs from Gram-positive bacteria revealed that PaPVA had a distinctive tetrameric structure and active site organization. In addition, mutagenesis of key active site residues and biochemical characterization of the resultant variants elucidated the role of these residues in substrate binding and catalysis. The importance of residue Trp23 and Trp87 side chains in binding and correct positioning of Pen V by PVAs was confirmed using mutagenesis and substrate docking with a 15 ns molecular dynamics simulation. These results establish the unique nature of Gram-negative CGHs and necessitate further research about their substrate spectrum. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Aromatic stacking; Cholylglycine hydrolase; molecular dynamics; Mutagenesis; Oligomeric interactions

Structural-functional insights and studies on saccharide binding of Sophora japonica seed lectin - Yadav, Priya; Shahane, Ganesh; Ramasamy, Sureshkumar; Sengupta, Durba; Gaikwad, Sushama (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of the Sophora japonica seed lectin (SJL) were studied in detail using bioinformatics and biophysical tools. Homology model of the lectin displayed all the characteristics of the legume lectin monomer and the experimental observations correlated well with the structural information. In silico studies were performed by protein-ligand docking, calculating the respective binding energies and the residues involved in the interactions were derived from LigPlot(+) analysis. Fluorescence titrations showed three times higher affinity of T-antigen disaccharide than N-acetyl galactosamine (GaINAc) towards SJL indicating extended sugar binding site of the lectin. Thermodynamic parameters of T-antigen binding to SJL indicated the process to be endothermic and entropically driven while those of GaINAc showed biphasic process. SDS-PAGE showed post-translationally modified homotetrameric species of the lectin under native conditions. In presence of guanidine hydrochloride (0.5-5.0 M), the tetramer first dissociated into dimers followed by unfolding of the protein as indicated by size exclusion chromatography, fluorescence and CD spectroscopy. Different structural rearrangements were observed during thermal denaturation of SJL at physiological pH 7.2, native pH 8.5 and molten globule inducing pH 1.0. Topological information revealed by solute quenching studies at respective pH indicated differential hydrophobic environment and charge density around tryptophan residues. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Dissociation; docking; Homology model; Ligand binding; Sophora japonica seed lectin; Thermal transitions

Structural insight into a membrane intrinsic Acyltransferase from Chlorobium tepidum - Boral, Debjyoti; Vankudoth, Koteswara Rao; Ramasamy, Sureshkumar (Current Microbiology, 2019)
The Lipid A component of the outer membrane of Gram-negative bacteria is an integral part of the permeability barrier known as LPS, which actively prevents the uptake of bactericidal compounds. It is clinically very significant, as it is known to elicit a strong immune response in the humans, through the TLR4 complex. The Lipid A species are synthesized through a highly conserved multistep biosynthetic pathway. The final step is catalyzed by acyltransferases of the HtrB/MsbB family, which are members of a superfamily of enzymes, present in all domains of life with important roles to play in various biological processes. The investigation of a putative dual functioning enzyme which can add both laurate and myristate residues to the (Kdo)(2)-lipid IVA (precursor of Lipid A) would give a snapshot into the versatility of substrates that these enzymes catalyze. In this study we have cloned and purified to homogeneity, such a putative dual functional acyltransferase from Chlorobium tepidum, and attempted to study the enzyme in more details in terms of its sequence and structural aspects, as it lacks conserved residues with other enzymes of the same family.

Structural insights into the unique inhibitory mechanism of Kunitz type trypsin inhibitor from Cicer arietinum L. Vol. 37 - Bendre, Ameya D.; Suresh, C. G.; Shanmugam, Dhanasekaran; Ramasamy, Sureshkumar (Journal of Biomolecular Structure & Dynamics, 2019)
Kunitz-type trypsin inhibitors bind to the active pocket of trypsin causing its inhibition. Plant Kunitz-type inhibitors are thought to be important in defense, especially against insect pests. From sequence analysis of various Kunitz-type inhibitors from plants, we identified CaTI2 from chickpea as a unique variant lacking the functionally important arginine residue corresponding to the soybean trypsin inhibitor (STI) and having a distinct and unique inhibitory loop organization. To further explore the implications of these sequence variations, we obtained the crystal structure of recombinant CaTI2 at 2.8 angstrom resolution. It is evident from the structure that the variations in the inhibitory loop facilitates non-substrate like binding of CaTI2 to trypsin, while the canonical inhibitor STI binds to trypsin in substrate like manner. Our results establish the unique mechanism of trypsin inhibition by CaTI2, which warrant further research into its substrate spectrum.
Keywords: Chickpea; crystal structure; inhibitory loop; Kunitz trypsin inhibitor; Trypsin

Structural and enzymatic analysis of a dimeric cholylglycine hydrolase like acylase active on N-acyl homoserine lactones - Philem, Pushparani D.; Yadav, Yashpal; Sunder, Avinash Vellore; Ghosh, Deepanjan; Prabhune, Asmita; Ramasamy, Sureshkumar (Biochimie, 2020)
The prevalence of substrate cross-reactivity between AHL acylases and beta-lactam acylases provides a glimpse of probable links between quorum sensing and antibiotic resistance in bacteria. Both these enzyme classes belong to the N-terminal nucleophile (Ntn)-hydrolase superfamily. Penicillin V acylases alongside bile salt hydrolases constitute the cholylglycine hydrolase (CGH) group of the Ntn-hydrolase superfamily. Here we report the ability of two acylases, Slac1 and Slac2, from the marine bacterium Shewanella loihica PV4 to hydrolyze AHLs. Three-dimensional structure of Slac1 reveals the conservation of the Ntn hydrolase fold and CGH active site, making it a unique CGH exclusively active on AHLs. Slac1homologs phylogenetically cluster separate from reported CGHs and AHL acylases, thereby representing a functionally distinct sub-class of CGH that might have evolved as an adaptation to the marine environment. We hypothesize that Slac1 could provide the structural framework for understanding this subclass, and further our understanding of the evolutionary link between AHL acylases and beta-lactam acylases. (C) 2020 Elsevier B.V. and Societe Francaise de Biochimie et Biologie Moleculaire (SFBBM). All rights reserved.
Keywords: AHL acylase; Cholyolglycine hydrolase; Homodimer; Ntn-fold; Shewanella loihica-PV4

Structure and regulation of SWEET transporters in plants: an update - Anjali, Anjali; Fatima, Urooj; Manu, M. S.; Ramasamy, Sureshkumar; Senthil-Kumar, Muthappa (Plant Physiology and Biochemistry, 2020)
Sugar will eventually be exported transporters (SWEETs), a novel family of sugar transporters found in both eukaryotes and prokaryotes, facilitate sugar flux across the cell membrane. Although these transporters were first discovered in plants, their homologs have been reported in different organisms. SWEETs have critical roles in various developmental processes, including phloem loading, nectar secretion, and pathogen nutrition. The structure of bacterial homologs, called SemiSWEETs, has been well studied thus far. Here, we provide an overview of SWEET protein structure and dynamic function by analyzing the solved crystal structures and predicted models that are available for a few SWEETs in a monocot plant (rice) and dicot plant (Arabidopsis thaliana). Despite the advancement in structure-related studies, the regulation of SWEETs remains unknown. In light of reported regulatory mechanisms of a few other sugar transporters, we propose the regulation of SWEETs at the post-translational level. We then enumerate the potential post-translational modification sites in SWEETs using computational tools. Overall, in this review, we critically analyze SWEET protein structure in plants to predict the post-translational regulation of SWEETs. Such findings have a direct bearing on plant nutrition and defense and targeting the regulation at these levels will be important in crop improvement.
Keywords: oligomerization; Phosphorylation; Post-translational modification; Sugar transporters; Sugar will eventually be exported transporters